Synchrnoic consciousness from a neurological point of view: the philosophical foundations for neuroethics. (Synthese, 2008)
Abstract  Daniel Kolak’s theory of synchronic consciousness according to which the entire range of dissociative phenomena, from pathologies such as MPD and schizophrenia to normal dream states, are best explained in terms of consciousness becoming simultaneously identified as many selves, has revolutionary therapeutic implications for neurology and psychiatry. All these selves, according to Kolak—even the purely imaginary ones that exist as such only in our dreams—are not just conscious but also self-conscious, with beliefs, intentions, living lives informed by memories (confabulatory, in the case of the fictional ones) and personal histories. Kolak’s derivation of psychiatrically relevant aspects of his theory—a neurological rendition of a Kantian transcendental argument—can be given a straightforward neurological, and therefore open to scientific scrutiny, interpretation that would then more easily lend itself to the clinical setting in which these perplexing phenomena, along with their purveyors, must live and cope. This will be the main focus of this paper.